ISLAMIC THOUGHT ON TECHNOLOGY AND ITS RELEVANCE TO HR MANAGEMENT - Lubis, Muhlisah; Udin, Zainuddin; Kholijah, Siti (ILMU USHULUDDIN, 2025)
This article discusses the role of technology in classical and contemporary Islamic thought and its implications for human resource management (HRM). In classical Islamic thought, principles such as justice (adl), trust (amanah), and consultation (syura) serve as ethical foundations that guide the management of society and organizations in a fair and wise manner. This thought teaches that technology should be used for the welfare of the community and should not contradict Islamic moral values. Meanwhile, contemporary Islamic thought adapts these concepts to the development of modern technology, emphasizing the importance of innovation that brings social and economic benefits, as well as prioritizing justice and transparency in its implementation. In the context of HR management, the integration of classical and contemporary Islamic thought allows for the use of technology to enhance efficiency, accountability, and employee empowerment without compromising ethical principles. The use of tools such as artificial intelligence (AI) for recruitment and performance evaluation, as well as cloud-based management platforms, can help create a management system that is more transparent, efficient, and equitable. This article also discusses the challenges in implementing technology that aligns with Islamic values, such as personal data protection and reducing bias in technology-based systems. In conclusion, the integration of classical and contemporary Islamic thought in technology-based human resource management not only promotes organizational efficiency but also ensures that technology is used for the benefit of the community, in accordance with the principles of justice, trust, and consultation in Islam.